2015
DOI: 10.1590/s0102-67202015000200005
|View full text |Cite
|
Sign up to set email alerts
|

Adequate lymphadenectomy for colorectal cancer: a comparative analysis between open and laparoscopic surgery

Abstract: BackgroundIn the surgical treatment of colorectal cancer, a lymphadenectomy is considered adequate when at least 12 lymph nodes are removed.AimTo evaluate whether videolaparoscopic surgery positively affects the rates of adequate lymphadenectomy.MethodsAn observational study was conducted with patients undergoing either open or videolaparoscopic surgery for colorectal cancer between 2008 and 2013. The following variables were collected: gender, age, tumor site, histology, degree of differentiation, tumor stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Adequate lymphadenectomy in colorectal cancer is essential to define the stage as well to plan the adjuvant therapy, especially for cases at stage III [8] . Furthermore, several studies have demonstrated that adequate lymph node retrieval might be associated with a reduced risk of death and an improved survival rate [3,9] . The results of our study show that in more than half of the patients (57.5%), the number of the evaluated lymph nodes was below the current standard number of 12, with a mean and median of 10.7 (± 5.6) and 10 in the examined lymph nodes, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate lymphadenectomy in colorectal cancer is essential to define the stage as well to plan the adjuvant therapy, especially for cases at stage III [8] . Furthermore, several studies have demonstrated that adequate lymph node retrieval might be associated with a reduced risk of death and an improved survival rate [3,9] . The results of our study show that in more than half of the patients (57.5%), the number of the evaluated lymph nodes was below the current standard number of 12, with a mean and median of 10.7 (± 5.6) and 10 in the examined lymph nodes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, adequate lymphadenectomy is defined as the presence of at least 12 lymph nodes in the surgical specimen. In this regard, previous studies have shown that a higher number of harvested lymph nodes is associated with increased survival rate [3] .…”
mentioning
confidence: 95%
“…Adequate lymphadenectomy in colorectal cancer is essential to de ne the stage as well as planning the adjuvant therapy, especially for cases at stage III (8). Furthermore, several studies have demonstrated that adequate lymph node retrieval might be associated with the reduced risk of death and the improved survival rate (3,9).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 16,660 new cases of colon and rectum cancer in men and 17,620 in women are estimated for 2016 in Brazil 2 . In locally advanced rectum cancer, survival after R0 resection is very good, and exenteration should be offered to patients with advanced primary or recurrent tumor, where resection is necessary in addition to total excision of the conventional mesorectum 6 .…”
Section: Introductionmentioning
confidence: 99%